FRANK 'N STAIN : A GRAPHIC NOVEL - Peters, Stephanie True, 1965-; Cano, Fernando (North Mankato, Minnesota : Stone Arch Books, an imprint of Capstone, 2022)
Frank tends the garbage heap in the monster realm and builds inventions out of garbage scraps, so when he invents a robot named Stain who wreaks havoc and angers the monster population Frank must convince everyone Stain is not a threat.
Keywords: Monsters -- Comic books, strips, etc; Monsters -- Juvenile fiction; Robots -- Comic books, strips, etc; Robots -- Juvenile fiction; Graphic novels; Comics (Graphic works); Humorous comics; Monster comics